Hubungan Keterampilan Membaca Pemahaman dan Keterampilan Menulis Teks Cerpen Siswa Kelas IX SMPN 2 Bukik Barisan Payakumbuh - Dona, Intan Rahma; R, Syahrul (Lembaga Yasin AlSys, 2023)
This study has three objectives: (1) to describe the level of reading comprehension skills of class IX students of SMPN 2 Bukik Barisan Payakumbuh, (2) to describe the level of short story writing skills of class IX students of SMPN 2 Bukik Barisan Payakumbuh, and (3) to describe the relationship between reading skills understanding and skills in writing short stories for class IX students of SMPN 2 Bukik Barisan Payakumbuh. This type of research is quantitative research with descriptive methods. Based on data analysis, reading comprehension skills greatly influence the short story writing skills of class IX students of SMPN 2 Bukik Barisan.